Epidemiological Pattern of Newly Diagnosed Children with Type 1 Diabetes Mellitus, Taif, Saudi Arabia - Naglaa Mohamed Kamal Alanani; Adnan Amin Alsulaimani (The Scientific World Journal)
Introduction and Aim. Type-1-diabetes mellitus (T1DM) is the most commonly diagnosed type of DM in children and adolescents. We aim to identify the epidemiological profile, risk factors, clinical features, and factors related to delayed diagnosis or mismanagement in children with newly diagnosed T1DM in Taif, Saudi Arabia. Patients and Methods. Ninety-nine newly diagnosed patients were included in the study along with 110 healthy controls. Patients were classified into 3 groups (I: >2 years, II: 2–>6 years, and III: 6–12 years). Both patients and controls were tested for C-peptide, TSH, and autoantibodies associated with DM and those attacking the thyroid gland. Results. Diabetic ketoacidosis was present in 79.8%. Delayed and missed diagnoses were recorded in 45.5%, with significant correlation to age and district of origin. Severity at presentation showed significant correlation with age and cow’s milk feeding. Group I, those with misdiagnosis or positive DM related autoantibodies, had more severe presentations. The correlation of C-peptide and TSH levels in patients and controls was significant for C-peptide and nonsignificant for TSH. Conclusion. Misdiagnosis and mismanagement are common and account for more severe presentation, especially in young children >2 years. Early introduction of cow’s milk appears to be a risk factor for the development of T1DM.